Advancements in Isoniazid-Based Heterocyclic Derivatives as Potent Antitubercular Agents: A Comprehensive Review of Synthesis, SAR, and Biological Activity (2017–2023) - Garg, Mansi; Verma, Ekta; Mishra, Shweta; Sahu, Adarsh (Synlett, 2025)
Tuberculosis (TB) continues to be a major health problem worldwide, requiring the development of new and innovative therapeutic agents. Isoniazid (INH) is one of the drugs of choice for treating tuberculosis. It is activated by KatG, which produces nicotinamide adenine dinucleotide (NAD). The resulting metabolites inhibit enoyl-acyl carrier protein (ACP) reductase (InhA), an enzyme involved in the biosynthesis of mycolic acid in Mycobacterium tuberculosis. This inhibition disrupts the production of type II fatty acids, which are essential for mycolic acid synthesis and cell survival. However, INH-resistant mycobacterial strains are becoming more prevalent, primarily due to long-term, widespread use and misuse. Researchers have extensively researched and modified INH, a cornerstone in TB treatment, to improve its efficacy and reduce resistance. Numerous investigations have shown that heterocyclic scaffolds, when coupled with INH, exhibit excellent antitubercular activity by increasing the permeation of the drug into bacterial cells. The review highlights various heterocyclic moieties, including phenylisoxazole, indanyl, indole, and isatin, emphasizing their role in improving pharmacokinetic properties and overcoming drug resistance. Here, we have focused on INH-clubbed heterocyclic derivatives that were investigated from 2018 to 2023 as potential antitubercular agents. This review aims to guide future research and development of INH-based heterocyclic derivatives, offering a valuable resource for researchers in the quest for more effective antitubercular therapies.1 Introduction2 Challenges with Current Drug Treatment3 Literature Reports on INH-Clubbed Heterocyclic Derivatives4 Conclusion5 Abbreviations
Keywords: isoniazid; heterocycles; antituberculosis; drug resistance